2011
DOI: 10.1007/s11547-011-0666-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between MRI with spin-echo echo-planar diffusion-weighted sequence (DWI) and histology in the diagnosis of soft-tissue tumours

Abstract: In our experience, DWI with qualitative and quantitative analysis correlated well with histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
0
20
2
Order By: Relevance
“…ADC is an established marker of tumour cellularity (highly cellular regions have low ADC values), 24 and ADC mapping has been used to investigate the benignity and malignancy of lesions. 25 In the present study, the maximum and mean ADC values were found to be significantly associated with the presence of residual tumour (p , 0.05), although the presence or absence of a low signal region on ADC maps was also found to be significant. Many authors who have studied the ADC values of various benign and malignant tumours have concluded that the mean ADC values of benign soft-tissue tumours and malignant soft-tissue tumours overlap.…”
Section: Discussioncontrasting
confidence: 47%
“…ADC is an established marker of tumour cellularity (highly cellular regions have low ADC values), 24 and ADC mapping has been used to investigate the benignity and malignancy of lesions. 25 In the present study, the maximum and mean ADC values were found to be significantly associated with the presence of residual tumour (p , 0.05), although the presence or absence of a low signal region on ADC maps was also found to be significant. Many authors who have studied the ADC values of various benign and malignant tumours have concluded that the mean ADC values of benign soft-tissue tumours and malignant soft-tissue tumours overlap.…”
Section: Discussioncontrasting
confidence: 47%
“…ADC mapping has been explored for the differentiation of benign from malignant lesions in the musculoskeletal system by exploiting potential differences in cellularity between benign and malignant abnormalities (47). In addition, after any event that has caused a change in the amount of water within a tissue, such as may be due to tumor growth, neovascularity, or tumor necrosis (19), changes in signal intensity on the DW images are naturally expected (Fig 2c, 2i).…”
Section: Proton Mr Spectroscopy (Metabolic Technique)mentioning
confidence: 99%
“…They and others found apparent diffusion coefficient values of benign soft tissue masses and malignant soft tissue tumors not significantly different, making the differentiation between benign and malignant impossible . The use of T1‐ and T2‐weighted MRI has been compared with DWI in the diagnosis of soft tissue tumors …”
Section: Discussionmentioning
confidence: 99%